Perceptions par les enseignants d’une approche phénoménologique du tutorat entre élèves à l’école primaire - Sylvain Connac (Recherches en Éducation)
A help, mutual aid and peer tutoring device introduced within a class consists of giving pupils the opportunity to ask a fellow pupil for support when they are lacking. These cooperative organizations are studied in a variety of ways in the elementary school. First, this article describes how we employ phenomenological methodologies, built from a combination of photo and video data collection, self-confrontation interviews with pupils, and collaborative analyses with primary school teachers. This article then presents a synthesis of a series of interviews with teachers who have experienced these scientific approaches. It reveals the necessary methodological precautions as well as the effects of listening to pupils' talk on the professional development of primary school teachers.